Building a Stronger Backbone: 3D Printing's Role in Treating Spinal Cord Conditions - Jader, Arwa; Buccilli, Barbara; Kumar, Danisha; Atallah, Oday; Munir, Luqman; Almealawy, Yasser F.; Ennabe, Michelle; Joshi, Neil; Imdad, Urooj; Alan, Albert; Weinand, Martin (Asian Journal of Neurosurgery, 2024)
Spinal cord injuries (SCIs) pose significant challenges as complete nerve regeneration remains limited. The demand for improved technologies in SCI treatment is evident. One such emerging technology is three-dimensional printing (3DP), which, coupled with advancements in medical imaging and bioengineering, has significantly enhanced precision in surgical procedures. This systematic review aims to explore 3DP as a treatment option for SCIs, examining its cost, efficacy, safety, and the associated technological constraints. A systematic search of Medline was conducted through PubMed for literature published since 2019. The search results were exported to Rayyan for abstract and full-text screening following predefined criteria. The risk of bias in the selected studies was assessed using the RoB2 tool and the Newcastle-Ottawa Scale. From a total of 89 articles screened, 11 studies met the eligibility criteria, collectively assessing 237 individuals with various types of SCIs, including lumbar degeneration, en bloc resection of thoracolumbar metastasis, adult spinal deformity, and cervical degeneration. These studies examined the utilization of 3DP devices such as hand orthosis, interbody fusion cages, lamellar titanium cages, artificial vertebral bodies, and others. Most of the reviewed studies reported positive treatment outcomes, with the actual procedure costs varying from $65 to $5,000. Recent literature shows positive outcomes in the use of 3DP technologies for SCIs, highlighting its potential for enhancing both surgical and nonsurgical interventions. These advancements usher in a new era in SCI treatment, providing enhanced precision and a wider range of treatment options, ultimately leading to more comprehensive and effective patient care.
Keywords: 3D bioprinting; SCI surgery; bioengineering; cost-efficiency; neuroregeneration